The prevalence rate, mortality, and 5-year overall survival of Schistosoma japonicum patients with human malignancy - Liu, Xue-Fei; Ju, Shuai; Wang, Ke-Ying; Li, Ying; Qiang, Jin-Wei (Frontiers in Oncology, 2023)
Background: Only a few studies focused on the association between Schistosoma japonicum (S. japonicum) and human malignancy. The aim of this study was to update on the prevalence rate, mortality, and 5-year overall survival of S. japonicum patients with human malignancy. Methods: From January 20, 2018, to January 31, 2021, 5866 inpatients were included in the study. 656 S. japonicum patients with malignancy were identified. Cases were stratified by gender and age groups. The cancer sites, prevalence rate, mortality, and 5-year overall survival of the patients were reported. The S. japonicum patients with malignancy were further divided into non-digestive system tumor group (n = 309) and digestive system tumor group (n = 347) including esophagus, stomach, colon, rectum, liver, gallbladder, bile duct and pancreas cancer. Chi-squared test and odds ratio with confidence intervals were performed between these two groups. Results: Lung cancer was found the most common malignancy, which accounting for 18.6% of all malignancies and followed by colon-rectum, stomach, liver, and gallbladder cancer. These five-leading malignancies accounted for about 61.8% of all cases. Colon-rectum cancer was the leading cause of malignancy death, followed by lung, stomach, gallbladder, and liver cancer. These five-leading causes of deaths accounted for about 55.6% of all death cases. Statistically significant was found in the prevalence rate between S. japonicum and non-S. japonicum patients with/without digestive system tumor (P < 0.001). The odds ratio of S. japonicum patients with digestive system tumor was 1.6 (95%CI: 1.4-1.9). Conclusion: S. japonicum contributes to a significant prevalence and mortality in digestive system tumors, including colon-rectum, stomach, liver, and gallbladder cancer.